The New Defense Accords Put to the Test by the African Crisis - (:unkn) unknown (My University, 2013)
France is now refraining from conducting direct military interventions in Africa. This is, in part, due to the content of the defense accords of the “new generation.” However, this approach is fraught with historical and political burdens, as well as moral constraints. Therefore, the conflicts of Central Africa, Chad, and Mali are forcing Paris to take the role of policemen regarding support strategies of weak and threatened states.
Keywords: African Research